2018
DOI: 10.3390/ijms19030871
|View full text |Cite
|
Sign up to set email alerts
|

Treatment, Therapy and Management of Metabolic Epilepsy: A Systematic Review

Abstract: Metabolic epilepsy is a metabolic abnormality which is associated with an increased risk of epilepsy development in affected individuals. Commonly used antiepileptic drugs are typically ineffective against metabolic epilepsy as they do not address its root cause. Presently, there is no review available which summarizes all the treatment options for metabolic epilepsy. Thus, we systematically reviewed literature which reported on the treatment, therapy and management of metabolic epilepsy from four databases, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 55 publications
0
16
0
4
Order By: Relevance
“…In addition to the influence of nutritional status, the metabolism of the skeletal system in children is also affected by multiple factors such as chronic disease, drugs, and outdoor exercise time [24,25]. Valproic acid has been used as one of the traditional agents to control epileptic seizures in children [2,13]. As early as 2003, one…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the influence of nutritional status, the metabolism of the skeletal system in children is also affected by multiple factors such as chronic disease, drugs, and outdoor exercise time [24,25]. Valproic acid has been used as one of the traditional agents to control epileptic seizures in children [2,13]. As early as 2003, one…”
Section: Discussionmentioning
confidence: 99%
“…Although antiepileptic drugs (AEDs) do not have a "curative effect" on epilepsy, they control seizures. Valproic acid has been widely used as a long term anti epileptic medication [2], as it displays a certain effects in absence seizures, clinical depression, tonic-clonic seizures, juvenile myoclonic epilepsy and complex partial seizures [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to the relations between epilepsy and metabolism, there are reports and extensive reviews in the literature on the so-called "Metabolic Epilepsy", which is defined by the Lee group in 2018 as "is a metabolic abnormality which is associated with an increased risk of epilepsy development in affected individuals" (64). Even more important, as the above authors are describing, it seems that the commune drugs used for treating "normal" epilepsy, are not working in this case, since the mechanistics behind these two are quite different (64). It also seems that diet could be playing an important part in the management of this specific disorder (65).…”
Section: Metabolic Relevance and The "Metabolic Epilepsy"mentioning
confidence: 99%
“…It also seems that diet could be playing an important part in the management of this specific disorder (65). In fact, in an extensive recent review no less than 14 main mecanistical causes were identified such as: biotinidase deficiency, cerebral folate deficiency, creatine-related disorders, disorders of the urea cycle, folinic acid-responsive seizures, glucose transporter type 1 deficiency syndrome, glutaric aciduria, mitochondrial disorders, molybdenum cofactor deficiency, non-ketotic hyperglycaemia, peroxisomal-related disorders, pyridoxine-dependent epilepsy/ pyridox(am)ine-5′-phosphate oxidase-related deficiency and succinic semialdehyde dehydrogenase (SSADH) Deficiency (64).…”
Section: Metabolic Relevance and The "Metabolic Epilepsy"mentioning
confidence: 99%